A note on completing quasi-distance and distance matrices - Zhang, Yu-Lin (2019)
We give a necessary and su cient condition for the existence of a quasi-distance matrix where some positive o -diagonal entries have been prescribed. Moreover, we give an algorithm for obtaining such a matrix. We analyze also the case where distances instead of quasi-distances are considered.